4-6x=2x+3

Simple and best practice solution for 4-6x=2x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4-6x=2x+3 equation:


Simplifying
4 + -6x = 2x + 3

Reorder the terms:
4 + -6x = 3 + 2x

Solving
4 + -6x = 3 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
4 + -6x + -2x = 3 + 2x + -2x

Combine like terms: -6x + -2x = -8x
4 + -8x = 3 + 2x + -2x

Combine like terms: 2x + -2x = 0
4 + -8x = 3 + 0
4 + -8x = 3

Add '-4' to each side of the equation.
4 + -4 + -8x = 3 + -4

Combine like terms: 4 + -4 = 0
0 + -8x = 3 + -4
-8x = 3 + -4

Combine like terms: 3 + -4 = -1
-8x = -1

Divide each side by '-8'.
x = 0.125

Simplifying
x = 0.125

See similar equations:

| 8-7x=53-42x | | .75+d=-.5 | | 28+m=-39 | | 50-g=47 | | 2x+7+8x+3= | | -13+t=-27 | | 8x+13y+50=180 | | m-18=-13 | | 35-4x=5x+22 | | 2(2x+1)=3x+9 | | y^2+6y-4=0 | | x^2+x^2=32 | | 2x-10=-45-9x | | 130-3x=6x+13 | | 4[3-3(x+1)]+1=2(-19-x)+2x+19 | | 81-4x=8x-21 | | y=-x^2(-20x)(-42) | | y=-x^2-20x-42 | | 3a=-9 | | 1+6(9-7x)-13x=-50x | | 3(8-2x)=-7x | | [-5.42]= | | 3b*1b=400 | | 6x+2x-5x-9+1=-5-2x+2 | | -2x=7x+7-5x-1-x+3x | | 7c+2=16 | | 3b*b+400=0 | | -2x=7x+7-5x-1-x | | 4x+4=7x-3+2+5+x | | 40n+36n-24= | | -15-3x=0 | | 12x-y=5 |

Equations solver categories